Better BMI but higher anemia risk? Evidence from lacto-vegetarian women - Hamid Nurrohman; Ha Thi Thu Trang (Public Health and Occupational Safety Journal, 2026)
Background: The increasing adoption of plant-based diets in the United States, particularly lacto-vegetarian patterns, has been driven by their perceived metabolic benefits. However, middle-aged women represent a nutritionally vulnerable group due to menopausal transitions and a high risk of anemia. In this context, the potential trade-off between improved body weight and micronutrient deficiencies remains insufficiently explored. Objectives: This study examined the nutritional trade-offs between lacto-vegetarian and non-vegetarian diets, focusing on body mass index (BMI), anemia status, and lifestyle behaviors among middle-aged women in California, USA. Methods: A cross-sectional study was conducted between June and September 2025 in California, USA, involving 40 women aged 40–65 years (20 lacto-vegetarians and 20 non-vegetarians), selected purposively. Socio-demographic characteristics and lifestyle behaviors were collected using a validated structured questionnaire. BMI, blood pressure, and hemoglobin levels were measured using standardized procedures. Data were analyzed using the Mann–Whitney U test and Spearman rank correlation, with results summarized using median and interquartile range (IQR) where appropriate. Statistical significance was set at p < 0.05. Results: Lacto-vegetarian women showed a higher proportion of normal BMI compared to non-vegetarians (50% vs 30%, p=0.04). However, anemia prevalence was markedly higher among lacto-vegetarians (70% vs 10%, p=0.001). No significant differences were observed in physical activity, smoking, or blood pressure (p>0.05). These findings indicate a clear nutritional trade-off: improved weight status is associated with increased anemia risk. Conclusions: Lacto-vegetarian diets were associated with more favorable BMI profiles but a significantly higher risk of anemia. These findings highlight the need for targeted nutritional strategies and public health interventions in the United States, particularly emphasizing iron and vitamin B12 adequacy among middle-aged women adopting plant-based diets.